Medical, Sensorimotor and Cognitive Factors Associated With Gait Variability: A Longitudinal Population-Based Study - Jayakody, Oshadi; Breslin, Monique; Srikanth, Velandai; Callisaya, Michele (Frontiers in Aging Neuroscience, 2018)
Abstract Background Greater gait variability increases the risk of falls. However, little is known about changes in gait variability in older age. The aims of this study were to: 1) examine change in gait variability across time and 2) factors that predict overall mean gait variability and its change over time. Methods Participants (n=410; mean age 72 years) were assessed at baseline and during follow up visits at an average of 30 and 54 months. Step time, step length, step width and double support time (DST) were measured using a GAITRite walkway. Variability was calculated as the standard deviation of all steps for each individual. Covariates included demographic, medical, sensorimotor and cognitive factors. Mixed models were used to determine 1) change in gait variability over time 2) factors that predicted or modified any change. Results Over 4.6 years the presence of cardiovascular disease at baseline increased the rate of change for step length variability (p=0.04 for interaction), lower education increased the rate of change for DST variability (p=0.04) and weaker quadriceps strength increased the rate of change for step width variability (p=0.01). Greater postural sway predicted greater variability on average across the 3 phases (p<0.05). Arthritis, a higher body mass index (BMI), slower processing speed and lower quadriceps strength predicted greater mean step time variability (p<0.05). Arthritis and a higher BMI predicted greater mean step length variability, while slower processing speed and BMI predicted greater mean DST variability (p<0.05) Conclusion Over a nearly five-year period, variability in different gait measures do not show uniform changes over time. Furthermore, each variability measure appears to be modified and predicted by different factors. These results provide information on potential targets for future trials to maintain mobility and independence in older age.